Global warming and food engineering emissions - Kolawole, P. (Scientific and Academic Publishing, 2012)
Pollution is the cause of global warming; this was linked with the world energy poverty, many countries of the world dependent on generators for electricity was blamed on inadequate clean energy supply. Food industries still depend on fossil fuels to power farm tractors and vehicles. Other developing nation’s dependant on fire woods leads to deforestation. Global warming is here, the bad effect is already happening, mostly the world’s poorest people are feeling the impact. Combustion processes in heat engines as one of the leading causes are not checkmated; gases from combustion of carbon compounds burns in oxygen, nitrogen and Carbon among others are major pollutants. Nitrogen yields nitrogen dioxide and Carbon yields carbon dioxide these are the pollutants playing major role in global warming. This is threatening human pro-gress and making the United Nations’ Millennium Development Goals (MDGs) for poverty reduction unachievable. The food industries and engineering involved in food production need cleaner and safe energy to reduce this pollution.